(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the adjunctive efficacy of Pegos Gingival mouthwash for dental plaque control in patients with plaque-induced gingivitis. Methods: A double-blind, randomized controlled clinical trial was conducted in 123 participants assigned to an intervention group (Pegos Gingival) or a control group (0.9% NaCl). Plaque accumulation was assessed at baseline and at 2 and 4 weeks using the Turesky Modification of the Quigley–Hein Index (TMQHI). Between-group comparisons were performed for TMQHI category distribution and mean TMQHI scores. Results: At week 4, the distribution of TMQHI categories (very low, low, moderate, high) was 47.6%, 31.7%, 17.5%, and 3.2% in the intervention group versus 15.0%, 53.3%, 20.0%, and 11.7% in the control group (p < 0.001). Mean TMQHI at week 4 was lower in the intervention group than in the control group (1.13 ± 0.92 vs. 1.74 ± 0.86). Conclusion: Pegos Gingival mouthwash demonstrated an adjunctive benefit in plaque control, resulting in significantly lower plaque accumulation than 0.9% NaCl after 4 weeks.